2001
DOI: 10.2458/azu_jrm_v54i1_engle
|View full text |Cite
|
Sign up to set email alerts
|

Viewpoint: The response of central North American prairies to seasonal fire

Abstract: Natural fires on the native grasslands of Oklahoma and Kansas were important for maintaining ecosystem structure and function. Today, land managers largely conduct prescribed fires in the late dormant season or they do not burn at all. When wildfires occur in other seasons, conventional wisdom assumes that desirable forage species for cattle are compromised. This assumption is based on a few fire studies limited in breadth and scope. To address this, we revisited numerous data sets to quantify the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…In the Willamette Valley, fire application is often pushed to the latter portion of the seasonal burn window to allow for full maturation and senescence of many high fidelity prairie and savanna herbaceous species that are still setting seed in September and October, such as Perideridia montana (common yampah), Symphiotrichum hallii (Hall's aster), Sericocarpus rigidus (Columbian white-top aster) and Pyrrocoma racemosa (clustered goldenweed). Land managers and researchers in the central U.S. tallgrass prairie have found that burning at different times can select for vastly different vegetation communities (Engle 2000, Engle andBidwell 2001). In (Bidwell et al 1990, Bidwell andEngle 1992), fire frequency (Blair 1997, Emery andGross 2004) and topography (Abrams et al 1986).…”
Section: Fire Seasonmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Willamette Valley, fire application is often pushed to the latter portion of the seasonal burn window to allow for full maturation and senescence of many high fidelity prairie and savanna herbaceous species that are still setting seed in September and October, such as Perideridia montana (common yampah), Symphiotrichum hallii (Hall's aster), Sericocarpus rigidus (Columbian white-top aster) and Pyrrocoma racemosa (clustered goldenweed). Land managers and researchers in the central U.S. tallgrass prairie have found that burning at different times can select for vastly different vegetation communities (Engle 2000, Engle andBidwell 2001). In (Bidwell et al 1990, Bidwell andEngle 1992), fire frequency (Blair 1997, Emery andGross 2004) and topography (Abrams et al 1986).…”
Section: Fire Seasonmentioning
confidence: 99%
“…Many native grassland species have been found to benefit from fire, but only when it is applied during a particular season and paired with other restoration treatments (herbicide, mowing, native seeding) (Engle and Bidwell 2001, Suding and Gross 2006, Brudvig et al 2007, Simmons et al 2007, Stanley et al 2011). Because fire alone can also benefit several non-native invasive species, the current restoration challenge in many fire-adapted systems involves creating habitat for native prairie species while excluding or prohibiting invasion by non-natives.…”
Section: Future Directionsmentioning
confidence: 99%
“…Resprouting dynamics of perennial grasses are inXuenced by variation in Wre regime characteristics, including intensity (Engle and Bidwell 2001). In turn, Wre intensity is determined by fuel characteristics (Byram 1959;Alexander 1982), such as perennial grass abundance (Rossiter et al 2003) and the depth and dryness of soil organic matter or litter which inXuences heat penetration into soil and, thus, the amount of damage to bud banks.…”
Section: Introductionmentioning
confidence: 99%
“…While species composition differs in burned and grazed grasslands, these disturbances may be selecting for similar traits that are distributed among different species. However, the effects of grazing and fire on the abundance of plant functional traits may differ depending on both the frequency and the intensity of burns and grazing (Engle and Bidwell 2001, Briggs et al 2002, Heisler et al 2003. Changes in the fire regime can have strong effects on the species and trait composition of plant communities (Pausas 1999, Franklin et al 2001, Kahmen and Poschlod 2008.…”
Section: Introductionmentioning
confidence: 99%